Peran Pemberdayaan Ekonomi Digital Difa City Tour (Ojek Difa) Terhadap Kesejahteraan Penyandang Disabilitas Di Yogyakarta - Ririn Nopiah; Puji Amalia Islami (Universitas Bengkulu, 2022)
The digital economy has become an online platform for all social economic activities especially Indoneisa. Platform online have become a necessity for every individual’s life. The existence of the digital economy is a business opportunity as a digital tools to improve business performance and interact with consumers. In addition, the digital economy provides open access for everyone including for people with disabilities. Ojek Difa is one of the digital-based innovatiions pioneered by people with disabilities as inclusive-based online transportation services. Ojek Difa is expected to be able to improve the social and economic welfare of ppeople with disabilities. The method used in this research is descriptive qualitative by in-depth interview. The results of the study indicate that Ojek Difabel has a major influence on increasing the economic degree of the income of workers (with disabilities). The results showed an increase in the percentage of 27.3% in income more than Rp. 1,000,000 and 45.5% in the range of income from more than Rp. 500,000 to Rp. 1,000,000 after the presence of Ojek Difa.